2010
DOI: 10.1007/s13187-010-0123-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Colorectal Cancer Screening in Urban African American Clinic Patients: Differences by Gender and Screening Status

Abstract: African Americans have higher colorectal cancer (CRC) morbidity and mortality than whites, yet have low rates of CRC screening. Few studies have explored African Americans' own perceptions of barriers to CRC screening or elucidated gender differences in screening status. Focus groups were conducted with 23 African American patients between 50 and 70 years of age who were © Springer 2010 Correspondence to: Sarah Bauerle Bass, sbass@temple.edu. NIH-PA Author Manuscript NIH-PA Author Manuscript NIH-PA Author M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 19 publications
(15 reference statements)
5
88
1
5
Order By: Relevance
“…Previous research supports the importance of provider recommendations for CRC screening, and patients who have never completed CRC screening may need provider counseling before completing a FIT. 30 , 33 , [37][38][39] Our study has several limitations. First, it was conducted in a single organization with a somewhat homogenous population and few clinical sites.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous research supports the importance of provider recommendations for CRC screening, and patients who have never completed CRC screening may need provider counseling before completing a FIT. 30 , 33 , [37][38][39] Our study has several limitations. First, it was conducted in a single organization with a somewhat homogenous population and few clinical sites.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, this study did not stratify patients by prior screening behaviors, despite the fact that never-screened patients may have lower knowledge about CRC screening, tend to rely on physician recommendations, and have negative attitudes toward FOBT. [28][29][30][31][32][33] To address gaps in the evidence base, we conducted this study to determine the marginal effect of outreach (mailed FIT, reminders, and personal calls), compared to high-quality point-of-care strategies, on CRC screening among CHC patients with no screening history. Understanding the benefits of outreach over point-of-care strategies is important because of the resources required for outreach.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous qualitative studies have investigated perceptions and experiences with colorectal cancer screening participation (17)(18)(19)(20). These studies have identified factors that affect screening decisions, as well as barriers and facilitators of colorectal cancer screening in a variety of settings.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] This manifest lack of knowledge and its potential risks are clearly at least partly responsible for low screening rates. 8 Thus some people consider that CRC cannot be a serious disease, because if it were, they would be better informed.…”
Section: Lack Of Knowledge and Erroneous Beliefs About Colorectal Cancermentioning
confidence: 99%
“…17 Others seem to be unaware of the need for regular screening, or at least think that once is enough. 22 The Hemoccult-II ® test raises a large number of questions and strong reticence, 14 which very likely explains why it is the most infrequently used test. 20 It arouses considerable distrust due to its presumed lack of reliability, based on the feeling that only tests carried out by doctors guarantee a degree of credibility, 9 together with the fact that certain members of the medical profession question the test's sensitivity.…”
Section: Lack Of Knowledge and Erroneous Beliefs About Colorectal Cancermentioning
confidence: 99%